Respuesta :
Answer:
x=-9
Step-by-step explanation:
first you make the coefficients equal to each other by doing a common factor which in this case is 5. Then you have to do the variable for each time the common number is repeated which is 5^x * 5^x= 5^(x+3)*5^(x+3)*5^(x+3) This would make it equal to 5^2x=5^(3x+9). Since the non exponents are common factors you can get rid of them and solve for the exponent by doing 2x=3x+9. You solve that equation to get x=-9.
x = - 0.03
25x = 125x + 3
subtract 125x from both sides
25x - 125x = 125x - 125x + 3
-100x = 3
divide both sides by -100
x = 3 / -100
x = - 0.03
check here for similar problems: https://brainly.com/question/6636335?referrer=searchResults